Clinical spectrum of coronavirus disease 2019 in Iceland: population based cohort study. (2nd December 2020) - Eythorsson, Elias; Helgason, Dadi; Ingvarsson, Ragnar Freyr; Bjornsson, Helgi K; Olafsdottir, Lovisa Bjork; Bjarnadottir, Valgerdur; Runolfsdottir, Hrafnhildur Linnet; Bjarnadottir, Solveig; Agustsson, Arnar Snaer; Oskarsdottir, Kristin; Thorvaldsson, Hrafn Hliddal; Kristjansdottir, Gudrun; et al.
Abstract: Objective: To characterise the symptoms of coronavirus disease 2019 (covid-19). Design: Population based cohort study. Setting: Iceland. Participants: All individuals who tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by reverse transcription polymerase chain reaction (RT-PCR) between 17 March and 30 April 2020. Cases were identified by three testing strategies: targeted testing guided by clinical suspicion, open invitation population screening based on self referral, and random population screening. All identified cases were enrolled in a telehealth monitoring service, and symptoms were systematically monitored from diagnosis to recovery. Main outcome measures: Occurrence of one or more of 19 predefined symptoms during follow-up. Results: Among 1564 people positive for SARS-CoV-2, the most common presenting symptoms were myalgia (55%), headache (51%), and non-productive cough (49%). At the time of diagnosis, 83 (5.3%) individuals reported no symptoms, of whom 49 (59%) remained asymptomatic during follow-up. At diagnosis, 216 (14%) and 349 (22%) people did not meet the case definition of the Centers for Disease Control and Prevention and the World Health Organization, respectively. Most (67%) of the SARS-CoV-2-positive patients had mild symptoms throughout the course of their disease. Conclusion: In the setting of broad access to RT-PCR testing, most SARS-CoV-2-positive people were found to have mild symptoms. Fever and dyspnoea were less common than previously reported. A substantial proportion of SARS-CoV-2-positive people did not meet recommended case definitions at the time of diagnosis.